Tipos de humor en la publicidad impresa en Colombia (2005)
Humor is one of the most frequently used tools to persuade in advertising. Therefore, interest in studying humor's influence in the attitudes and behavior of individuals has increased. A revision of research projects regarding humor in advertising and its effects in persuation, attention, comprehension, attitudes and memory was performed as well as studies concerning humor and cultural factors, type of audience, media and type of product. A classification of humorous advertisement published in Colombia has been executed on account of bibliographical revisions and of the serialized tracking of the Semana Magazine; leading to the identification of three new categories. The proposed types of humor are: incongruity, hostile, surprise, pun, personification, phrases, allusions, comparation, rhymes, cartoons, skits and exaggeration. Index terms: advertising, humor in advertising, psychology, types of humor, attitudes.